Ovarian pregnancy: report of two cases - Bardales, María (2015)
Ovarian pregnancy is a rare localization of ectopic pregnancy, represented by different authors, 0.5 to 4% of extrauterine pregnancies with an incidence of about one in 7,000 pregnancies. It is the most common type of non tubérico ectopic pregnancy. Two cases of ovarian pregnancies communicates, presents symptoms, diagnosis method, applied therapy, pathologic examination, evolution and review of the literature and some relevant comments.